2022
DOI: 10.1155/2022/7599539
|View full text |Cite|
|
Sign up to set email alerts
|

Logistic Distribution Route Optimization Based on RFID and Sensor Technology

Abstract: In order to solve the problem that the traditional e-commerce logistic distribution path optimization algorithm takes a long time to find the optimal path, this paper presents the best ways for exporting based on RFID and sensor technology. First, the integration algorithm is used to divide the logistic area; then, the purpose of various goals to improve the performance of the export consists of five things: measuring weight, measuring time, measuring the importance of customers, window measuring time, and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Xin et al, [2] and Gan [3] respectively adopted genetic algorithm and hybrid intelligent algorithm to optimize logistics distribution routes, and these studies demonstrated the effectiveness of genetic algorithm in solving complex optimization problems. In addition, Ma and Wang [4] discussed the optimization of logistics distribution routes based on RFID and sensor technology, highlighting the application of IoT technology in real-time data tracking and processing. This is consistent with the focus of this study, which is to use IoT technology to optimize logistics distribution routes.…”
Section: Introductionmentioning
confidence: 99%
“…Xin et al, [2] and Gan [3] respectively adopted genetic algorithm and hybrid intelligent algorithm to optimize logistics distribution routes, and these studies demonstrated the effectiveness of genetic algorithm in solving complex optimization problems. In addition, Ma and Wang [4] discussed the optimization of logistics distribution routes based on RFID and sensor technology, highlighting the application of IoT technology in real-time data tracking and processing. This is consistent with the focus of this study, which is to use IoT technology to optimize logistics distribution routes.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%